SALMONELLA ABORTUSOVIS БАКТЕРИОФАГЫНЫҢ БИОЛОГИЯЛЫҚ ҚАСИЕТТЕРІН ЗЕРТТЕУ - М. Маталипова; Р. Саттарова; Е. Оспанов; Ф. Бакиева; Қ. Шыныбаев; А. Шолпанкулова; Қ. Машинқызы; А. Илимбаева; Ж. Тлегенова; А. Нурпейсова; М. Касенов; Н. Татришвили (Animal Health and Biosafety, 2026)
Currently, the increasing antibiotic resistance of Salmonella enterica strains is considered one of the major challenges in veterinary medicine and public health. In particular, Salmonella abortusovis is the causative agent of infectious processes in sheep characterized by abortion, septicemia, and high mortality among lambs. In this regard, the use of highly specific and effective bacteriophages as an alternative to antibiotics is regarded as one of the most promising approaches. The aim of this study was to isolate bacteriophages active against Salmonella abortusovis and to investigate their main biological properties.During the study, biological samples collected from farms, slaughterhouses, sewage systems, and sheep in Almaty city and Almaty region were examined. For the first time in Kazakhstan, a bacteriophage specific to the Salmonella abortusovis strain was isolated. The lytic activity of the isolated phages was evaluated using the Appelman and Gratia methods, demonstrating high lytic efficacy. The phage activity titer reached 10⁻⁶, while the number of phage particles in 1 cm³ was 4 × 10⁸ PFU/cm³. By the agar layer method, the phages formed transparent, colorless negative plaques with diameters ranging from 0.1 to 0.3 mm.In addition, the resistance of the bacteriophages to environmental factors was investigated. The results showed that the phages retained activity at temperatures up to 55 °C, remained stable within a pH range of 5–9, and were resistant to chloroform exposure for up to 15 minutes. The isolated Salmovir bacteriophage was characterized by high specificity, thermostability, and pronounced lytic activity. The obtained results provide a scientific basis for the potential application of bacteriophages against Salmonella abortusovis in the treatment and prevention of salmonellosis-associated abortion in sheep.